Historical perspectives and emerging trends in fentanyl use: Part 2 – overdose and misuse - Stanila Stoeva-Grigorova; Maya Radeva-Ilieva; Nadezhda Karkkeselyan; Stela Dragomanova; Gabriela Kehayova; Simeonka Dimitrova; Maria Petrova; Snezha Zlateva; Petko Marinov (Pharmacia)
The misuse of fentanyl and its analogs has significantly worsened the opioid crisis, leading to a sharp increase in overdose fatalities. Fentanyl overdose primarily causes severe respiratory depression, which can result in hypoxia, cardiac arrest, and death, often exacerbated by co-intoxication. Additionally, the opioid in question can induce chest wall rigidity, further complicating treatment procedures. Despite international control efforts, the drug’s high potency and low cost have fueled its widespread trafficking, including in counterfeit pills. While naloxone is the primary antidote, its effectiveness is limited, highlighting the need for stronger, long-acting treatments. Factors such as polypharmacy, prescription misuse, and environmental exposure – as well as the potential for fentanyl’s use as a chemical weapon – pose significant public safety risks. In conclusion, addressing the current wave of the opioid crisis requires a comprehensive approach, integrating treatment solutions, prevention, and harm reduction strategies.